2013
DOI: 10.1155/2013/425651
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health, Temporomandibular Disorder, and Masticatory Performance in Patients with Charcot‐Marie‐Tooth Type 2

Abstract: Background. The aim of this study was to evaluate the oral health status of temporomandibular disorders (TMD) and bruxism, as well as to measure masticatory performance of subjects with Charcot-Marie-Tooth type 2 (CMT2). Methods and Results. The average number of decayed, missing, and filled teeth (DMFT) for both groups, control (CG) and CMT2, was considered low (CG = 2.46; CMT2 = 1.85, P = 0.227). The OHIP-14 score was considered low (CG = 2.86, CMT2 = 5.83, P = 0.899). The prevalence of self-reported TMD was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…32 Also, the absence of sleep bruxism in the PSG corroborates a previous study in this same family, in which the subjective complaint of clenching teeth associated with orofacial pain was not observed. 35 In the sleep architecture, our study showed no important changes in sleep latency, although most patients reported difficulty in initiating sleep in the PSQI questionnaire. However, there was an increase of WASO (%) and arousals, suggesting a fragmented sleep pattern, contributing to the lower sleep efficiency (< 85%) found in 50% of the patients.…”
Section: Discussionmentioning
confidence: 48%
“…32 Also, the absence of sleep bruxism in the PSG corroborates a previous study in this same family, in which the subjective complaint of clenching teeth associated with orofacial pain was not observed. 35 In the sleep architecture, our study showed no important changes in sleep latency, although most patients reported difficulty in initiating sleep in the PSQI questionnaire. However, there was an increase of WASO (%) and arousals, suggesting a fragmented sleep pattern, contributing to the lower sleep efficiency (< 85%) found in 50% of the patients.…”
Section: Discussionmentioning
confidence: 48%
“…Acidic environments can trigger enamel demineralization, which might result in dental issues and worsen TMD symptoms. 23 Cortisol and other stress-related indicators can be found in saliva. For those who are sensitive, chronic stress and its effects on saliva composition may affect muscle tension and exacerbate the symptoms of TMD.…”
Section: Introductionmentioning
confidence: 99%
“…The oral environment may change as a result of pH and buffering capacity changes in saliva. Acidic environments can trigger enamel demineralization, which might result in dental issues and worsen TMD symptoms 23 . Cortisol and other stress‐related indicators can be found in saliva.…”
Section: Introductionmentioning
confidence: 99%